PENGENDALIAN KAS PADA PT. EXSOL INNOVINDO - Safitri, Emi Suci (EKONOMIA, 2014)
Based on research results of the internal control system of cash at PT. Exsol Innovindo adequate. this is supported by the elements; organization, authorization, healthy practices and placement of employees.so the authors put forward the hypothesis that the organization, authorization, healthy practices, and placement of employees in PT. Exsol Innovindo are in accordance with the standard operating procedures of internal control and cash are accepted